Clinical characteristics, pathology features and outcomes of pediatric myeloid sarcoma: A retrospective case series - Ye, Fanghua; Zhang, Hui; Zhang, Wen; Dong, Jiajia; Deng, Wenjun; Yang, Liangchun (Frontiers in Pediatrics, 2022)
Purpose: Myeloid sarcoma (MS) is a rare extramedullary mass with myeloid expression, which is easy to be missed and misdiagnosed, especially in the pediatric population. We analyze the clinicopathological characteristics, immunophenotypic, cytogenetic, and molecular studies, therapeutic approaches, and outcomes, to optimize the management of such patients. Methods: A retrospective, single-center, case series study of eleven children diagnosed with MS by pathology was performed. Results: The male-to-female ratio was 8:3, and the median age at diagnosis was 7 years. The most commonly involved sites were the skin and orbital region, followed by lymph nodes, central nervous system, and testis. Seven cases (64%) with Class I-MS and four cases (36%) presented as Class II-MS. Immunohistochemically, MPO and CD117 were the most commonly expressed markers, followed by CD33, CD43, CD34, CD68, and lysozyme. Chromosomal abnormalities were detected in 4 patients. Two patients had the presence of deleterious mutations (FLT3, ASXL, KIT, and DHX15) on molecular detection. Ten patients were treated with chemotherapy based on AML regimens. The median follow-up time was 33.5 months in eleven patients. two patients relapsed, one died, and one lost to follow-up. The 2-year overall survival (OS) rate estimated by Kaplan-Meier curves was 90.9% ± 8.7%, and the event-free survival (EFS) rate was 64.9% ± 16.7%. Conclusions: MS diagnosis is usually challenging. Adequate tumor biopsy and expanded immunohistochemistry are necessary for the correct diagnosis of MS. Early and regular systemic chemotherapy promises long-term survival.